Computational study of noble metal alloys - Popoola, Adewumi Isaac (My University, 2014)
The elastic constants, phase stability, heat of formation and the Debye temperature of various noble metal compounds in the stoichiometry A3B (where A = Pt, Ir, Rh, Ru, Pd and B = Al, Hf, Zr, Sc) were studied using the ab initio Density Functional Theory - Projector Augmented Wave method. A total of 24 compositions was investigated, of which 16 compounds were predicted to be thermodynamically stable. The remaining eight compounds were found not energetically favorable, due to positive or low heats of formation. According to the Density of States studies, the L12 structure was predicted in 8 compounds while four compounds had the D024 structure. Among compounds with the L12 structure, the hardest phase predicted was L12-Ir3Hf. L12-Pd3Sc was predicted as the least hard and most ductile compound. In compounds with the D024 structure, Pt3Zr was predicted having highest hardness and highest melting point. In all the compounds, the strongest interaction was found between hafnium and the noble metals and least interaction was with aluminum. The melting points from ab initio and molecular dynamics calculations slightly over-predicted experimental values, but showed the same trends. Both the fracture toughnesses and the melting points deduced using the Sutton-Chen potentials had similar trends to ab initio results, suggesting that the Sutton-Chen potentials is adequate for simulating metallic phases.
Keywords: Precious metals.; Precious metals - Experiments.